Comparison of AATSR and SEVIRI aerosol retrievals over the northern Adriatic - Thomas, G; Poulsen, C; Curier, R; de Leeuw, G; Marsh, S; Carboni, E; Grainger, R; Siddans, R (2007)
A case-study is presented comparing the Oxford-RAL retrieval of Aerosol and Cloud (ORAC) algorithm, applied to AATSR and Meteosat-8 SEVIRI data, and the dual-view AATSR aerosol retrieval developed at TNO. The study compares data from an AATSR overpass of the Northern Adriatic and Po Valley region on 4 September 2004, during which time there were two AERONET sunphotometer stations operating in the Venice region as part of the ADRIEX campaign. We present the results of a comparison of the optical depth determined from the two AATSR retrievals and the SEVIRI retrieval at the time of the AATSR overpass. The comparison shows that the satellite retrievals consistently overestimate the aerosol optical depth compared to the AERONET site. A possible reason for this over sea is an inability of the algorithms at present to take into account the ocean colour of coastal waters. Future improvements to the algorithms are suggested. Copyright © 2007 Royal Meteorological Society.